Trophic roles of Bufo bankorensis (Barbour 1908) tadpoles in an Asian subtropical stream. Issue 1 (2nd January 2019) - Wang, Yi-Kuang; Kam, Yeong-Choy
ABSTRACT: Tadpoles may be omnivorous with diverse trophic positions beyond herbivory, and may require multiple approaches for identification. Understanding the trophic and ecological roles of omnivorous tadpoles may require examination at a species level. The goals of this study were to determine the trophic positions of Bufo bankorensis tadpoles by using stable isotopes and food selection experiments, verify the tadpoles' effects on benthic resources with enclosure–exclosure experiments, and examine their role on nutrient cycling. Stable isotope experiments showed that B. bankorensis tadpoles fed on algae and animal items, indicating a trophic level close to that of a damselfly. The food selection experiments showed that the tadpoles fed on dead tadpoles and mayflies but not on live animals, making them necrophagous, and further testing revealed that the tadpoles preferred dead tadpoles over algae. In the enclosure–exclosure experiment, the tadpoles reduced the amounts of algae and organic matter and changed the compositions of algal growth forms. The tadpoles released nitrogen (N) into the ambient water, which was then recycled by benthic algae, as revealed by an 15 N addition experiment. We concluded that B. bankorensis tadpoles have trophic and ecological roles related to their trophic positions in a subtropical stream ecosystem.